Over-Expression of Inhibitor of Differentiation 2 Attenuates Post-Infarct Cardiac Fibrosis Through Inhibition of TGF-β1/Smad3/HIF-1α/IL-11 Signaling Pathway - Yin, Lin; Liu, Ming-xin; Li, Wei; Wang, Feng-yuan; Tang, Yan-hong; Huang, Cong-xin (Frontiers in Pharmacology, 2019)
Fibrosis after myocardial infarction(MI) often affects cardiac diastolic and systolic function, causing severe arrhythmia even sudden death. Inhibitor of differentiation 2(Id2), a transcriptional repressor, has been shown to play an important role in the fibrosis of a variety of substantial organs, but its effects in fibrosis of heart remains unclear. This study aimed to discover the influence of Id2 in cardiac fibrosis after myocardial infarction and its potential mechanism. Anoxic and fibrotic model for vitro experiment was established by using a three-gas incubator and TGF-β1, respectively. A myocardial infarction model was established by ligation of the left anterior descending coronary artery and then directing myocardial injection of Id2 adenovirus in the marginal zone of myocardial infarction was adopted. The results showed Id2-treated group could obviously improve cardiac function, decrease the accumulation of ECM, lessen cardiac hypertrophy and inhibit myofibroblast differentiation compared to MI group and GFP group. To further discover the mechanism, we found Id2 probably exerted protective effects through inhibiting TGF-β1/Smad3/hypoxia induced factor-1 alpha(HIF-1α)/interleukin (IL)-11 signaling pathways. Besides, Id2 can reduce cell apoptosis. In conclusion, over-expressed Id2 can keep preservation of cardiac function and ameliorate adverse cardiac remodeling, which might be a promising target for cardiac fibrosis and apoptosis.